Clinico-statistical survey of oral antimicrobial prophylaxis and surgical site infection regarding ordinary tooth extraction and mandibular wisdom tooth extraction in the dental outpatient clinic. Issue 2 (February 2021) - Yoshida, Kensuke; Kodama, Yasumitsu; Nagai, Takahiro; Estacio Salazar, Andrea Rei; Kaneko, Syouta; Saito, Chie; Toyama, Akira; Takagi, Ritsuo
Abstract: Introduction: We investigated the use of oral antibiotics (OA) and surgical site infection (SSI) related to extractions of ordinary teeth and mandibular wisdom teeth in a dental outpatient clinic from January 2015 to December 2019. Methods: The following information were surveyed: (1) presence/absence of OA, (2) timing, (3) type, (4) administration period, and (5) SSI rates. Results: The use of OA during ordinary tooth extraction decreased from 68.3% to 41.3%, but SSI rate did not change during this period of time. Total SSI rate was 0.8% (122/14, 832) on average. For mandibular wisdom tooth extraction, preoperative administration of third-generation cephalosporins decreased from 70.4% to 0.3% while that of penicillin (AMPC) increased from 0% to 98%. SSI rate was not changed after these improvements. Total SSI rate was 3.5% (180/5106) on average. The duration of OA was slightly decreased to two days in 2018 and 2019, and it was found that there was no significant difference in SSI rates between 2- and 3-day durations. Preoperative administration had 0.37 odds ratio (OR) (95% confidence interval (95%CI): 0.22–0.63) of SSI compared with postoperative administration. AMPC had 0.76 OR (95% CI: 0.55–1.04) of SSI compared with Third-generation cephalosporins and others. Timing of OA was P < 0.01. Conclusions: SSI rates did not change over time, administration period of OA decreased and the use of AMPC increased. Therefore, it seems necessary to continue to investigate the effects of SSI risk factors proactively in the future and to make efforts in the advocacy of appropriate antimicrobial use.